1979
DOI: 10.1017/s0022112079000392
|View full text |Cite
|
Sign up to set email alerts
|

Pressure-fluctuation measurements on an oscillating circular cylinder

Abstract: Measurements are presented of the fluctuating pressure recorded at a point 90° from the mean position of the forward stagnation point on a circular cylinder oscillating in a water flow. The aspect ratio of the cylinder was 9·5 and the turbulence level in the free-stream was 5·5%. The cylinder Reynolds number was 2·4 × 104 and the cylinder was forced to oscillate transverse to the main flow at amplitudes up to 1·33 cylinder diameters. The reduced velocity was varied over the range 3–18 and the experiments spann… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
39
0
1

Year Published

1985
1985
2007
2007

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(46 citation statements)
references
References 6 publications
6
39
0
1
Order By: Relevance
“…Their results showed a departure from two-dimensionality a short distance behind the cylinder that translated into more elongated and slightly weaker vortices, with a longer time averaged recirculation length. A slight phase difference between the two simulations was also observed and the 3D simulation showed better agreement with the experimental work of [10] at equivalent reduced velocity. Finally, the 3D simulation predicted smaller time averaged drag coefficient and absolute pressure than the 2D simulations and it was concluded that the deviations between the simulations were attributed to three-dimensionality of the wake.…”
Section: B Moving Cylinderssupporting
confidence: 53%
“…Their results showed a departure from two-dimensionality a short distance behind the cylinder that translated into more elongated and slightly weaker vortices, with a longer time averaged recirculation length. A slight phase difference between the two simulations was also observed and the 3D simulation showed better agreement with the experimental work of [10] at equivalent reduced velocity. Finally, the 3D simulation predicted smaller time averaged drag coefficient and absolute pressure than the 2D simulations and it was concluded that the deviations between the simulations were attributed to three-dimensionality of the wake.…”
Section: B Moving Cylinderssupporting
confidence: 53%
“…Bearman & Currie 1979;Williamson & Roshko 1988;Brika & Laneville 1993). While the sets of phenomena are undoubtedly related, a switch in timing associated with a change in sign of mechanical energy transfer cannot be observed in vortex-induced vibration experiments, at least not when the vibration and shedding are completely entrained and periodic.…”
Section: Phenomena Of Vortex-induced Vibrationmentioning
confidence: 99%
“…With the increase in Ur, the vortex with the same circulation is shed when the cylinder reaches the maximum amplitude on the same side. Bearman and Currie (1979), using controlled forced-vibration experiments at fixed amplitudes, have shown that although the significant change occurs over a small range of Ur, it is progressive and not a discontinuity.…”
Section: -44mentioning
confidence: 99%